Study on separation and dynamic characteristics of ilmenite and chlorite regulated by structural parameters of spiral chute - Shuling Gao; Bochao Li; Chunyu Liu; Qian Wang; Xiaohong Zhou; Guixia Fan; Daoguang Teng (Minerals Engineering, 2026)

Ethylene-triggered membrane lipid catabolism mediated by the PpERF110/113-PpPLD2 regulatory module exacerbates chilling injury in peach fruit - Lufan Wang; Huijuan Zhou; Qiaocai Zhang; Shiying Zhang; Zhengwen Ye; Xiongwei Li; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Lichao Zhou; Shuling Shen; Xiaolin Zheng; et al. (Postharvest Biology and Technology, 2026)

Designing sustained-release sodium carriers: Oil-modified starch gels enhance the texture and delay sodium release in low-sodium shrimp protein gels - Menghan Wang; Yang Li; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Chemistry, 2026)

Ultrasonically treated pea starch modulates oil absorption in corn starch-based deep-fried products: Insights into gel network architecture, interfacial behavior, and molecular dynamics simulations - Menghan Wang; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2026)

Methyl jasmonate alleviates chilling-induced browning in peach fruit through transcriptional suppression of PpLAC7 - Lufan Wang; Liang Zhou; Qiaocai Zhang; Huijuan Zhou; Lichao Zhou; Jiaxu Mao; Shiying Zhang; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Shuling Shen; Xiaolin Zheng; et al. (Postharvest Biology and Technology, 2026)

Engineering hydrodynamics via pitch-diameter ratio to intensify eco-efficient separation of fine hematite/quartz in spiral chute - Shuling Gao; Qian Wang; Xiaohong Zhou; Chunyu Liu; Bochao Li (Minerals Engineering, 2026)

Enhanced functionality and reduced allergenicity of silkworm pupae protein through Lactiplantibacillus plantarum fermentation - Jing Yang; Shuling Zhou; Yan Chen; Sutee Wangtueai; Jiajia Song (Food Chemistry, 2026)

Selection of adsorption and immobilization carriers under circulating flow conditions for enhanced performance and metabolic characteristics of Acidithiobacillus ferrooxidans - Fangzheng Zhou; Guanghui Chen; Yanyan Wang; Deshuang Yu; Yifan Zhu; Renjie Lu; Shufang Li; Shuling Xiao; Yingying Dong (Bioresource Technology, 2026)

AcERF61 transcription factor mediates ethylene-induced kiwifruit softening through directly regulating cell wall degradation genes - Lufan Wang; Jiaxu Mao; Shiying Zhang; Huijuan Zhou; Libin Wang; Liang Zhou; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2026)

Synergistic curdlan gum/xanthan gum system improves shrimp myofibrillar protein gel properties via enhanced network structure, texture and water holding capacity - Shuling Zhou; Xuening Yu; Menghan Wang; Xiaoyang Liu; Dayong Zhou (Food Research International, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Mechanisms of blue light-mediated inhibition of chlorophyll degradation in ‘Newhall’ sweet orange during postharvest - Hui Sun; Yuwei Zhou; Sijia Liu; Qianqian Yu; Mengyao Yin; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2026)

Exogenous melatonin activates BoNAC52-BoRBOHF module and antioxidant system involved in the delay in broccoli yellowing during postharvest - Yue Wang; Lufan Wang; Yuting Li; Wenbo Lei; Jianhui Cheng; Yuan Cheng; Shuling Shen; Lanying Yao; Lichao Zhou; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

Methyl jasmonate regulates the glycolytic pathway and the PpbZIP43-PpFAD2 module to enhance cold resistance in peach fruit - Lufan Wang; Yuxuan Wang; Jiaxu Mao; Huijuan Zhou; Libin Wang; Binger Dai; Liang Zhou; Shiying Zhang; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

1-MCP regulates taste development in cold-stored peach fruit through modulation of sugar, organic acid, and polyphenolic metabolism - Huijuan Zhou; Zhengwen Ye; Lufan Wang; Shiying Zhang; Ziyi Yuan; Mingshen Su; Xianan Zhang; Jihong Du; Xiongwei Li; Minghao Zhang; Yang Hu; Shuling Shen; et al. (Postharvest Biology and Technology, 2025)

Molecular interactions and physiological effects of oyster-derived synthetic peptide-calcium complex: Insight in improving the bone growth and health - Xuening Yu; Guang Li; Shijie Dou; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2025)

Effects of high hydrostatic pressure processing on the physicochemical properties, functional characteristics, and antioxidant activity of silkworm pupae protein - Jing Yang; Shuling Zhou; Yan Chen; Jiawang Jin; Jiajia Song (Food Chemistry, 2025)

Corrigendum to “Piezophotocatalysis of ZnO@PVDF coaxial nanofibers modified with BiVO4 and Ag for the simultaneous generation of H2O2 and removal of pefloxacin and Cr(VI) in water” [Chem. Eng. J. 484 (2024) 149514] - He Lv; Yanan Liu; Jianfeng Zhou; Yubin Bai; Hongpu Shi; Bin Yue; Shuling Shen; Deng-Guang Yu (Chemical Engineering Journal, 2025)

Application of edible insects to food products: A review on the functionality, bioactivity and digestibility of insect proteins under high-pressure/ultrasound processing - Jing Yang; Yan Chen; Linqing Zhang; Shuling Zhou; Linfeng You; Jiajia Song (Food Chemistry, 2025)

Control efficiency and potential mechanisms of chlorogenic acid against postharvest gray mold caused by Botrytis cinerea on peach fruit - Binger Dai; Yuxuan Wang; Huijuan Zhou; Lufan Wang; Liang Zhou; Jiaxu Mao; Shiying Zhang; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2024)

Edible insects as ingredients in food products: nutrition, functional properties, allergenicity of insect proteins, and processing modifications - Jing Yang; Shuling Zhou; Hong Kuang; Chunhong Tang; Jiajia Song (Critical Reviews in Food Science and Nutrition, 2024)

Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p

A review of the advances and prospects of aqueous Dual-Ion batteries - Shuhua Guan; Qiaoling Peng; Xiuli Guo; Ye Zheng; Enda Liao; Shuling Sun; Kyungsoo Shin; Botian Liu; Xiaolong Zhou; Caineng Zou; Yongbing Tang (Chemical Engineering Journal, 2024)

Post-earthquake repairability-based methodology for enhancing steel MRFs - Shuling Hu; Xuhong Zhou; Ke Ke; M. Shahria Alam; Taotao Shi (Engineering Structures, 2024)

Efficient piezophotocatalysis of ZnO@PVDF coaxial nanofibers modified with BiVO4 and Ag for the simultaneous generation of H2O2 and removal of pefloxacin and Cr(VI) in water - He Lv; Yanan Liu; Jianfeng Zhou; Yubin Bai; Hongpu Shi; Bin Yue; Shuling Shen; Deng-Guang Yu (Chemical Engineering Journal, 2024)

Real-time hybrid simulation incorporating machine learning for deep-water bridges subjected to seismic ground motion with fluid-structure dynamic interaction - Zihao Zhou; Dan Zhang; Yafei Zhang; Ning Li; Shuling Gao; Yanan Yue (Soil Dynamics and Earthquake Engineering, 2023)

Effects of Fermented Cottonseed Meal Substitution for Fish Meal on Intestinal Enzymatic Activity, Inflammatory and Physical-Barrier-Related Gene Expression, and Intestinal Microflora of Juvenile Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Xiaolin Huang; Heizhao Lin; Maoyan Luo; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2023)
The present study was conducted to investigate the effects of dietary fermented cottonseed meal (FCSM) substitution for fish meal on intestinal enzymatic activity, inflammatory and physical-barrier-related gene expression, and intestinal microflora of juvenile golden pompano. The 375 golden pompanos were divided into 15 groups of 25 fish each, with three replicates for each experimental group. The fish were fed five experimental diets (0 (FM), 12.5% (CSM12.5), 25% (CSM25), 50% (CSM50), and 100% (CSM100) substitution levels) for 8 weeks. The fish were reared and fed the experimental diets under a natural-day light cycle. Compared with the control group, the activities of AMY (amylase) enzymes in the CSM12.5 group and all other groups were elevated (p

Mechanistic insights into the detoxification of Cr(VI) and immobilization of Cr and C during the biotransformation of ferrihydrite-polygalacturonic acid-Cr coprecipitates - Hanyue Zhang; Yang Lu; Zhuozhi Ouyang; Wenjing Zhou; Xinyue Shen; Kun Gao; Shuling Chen; Yang Yang; Shiwen Hu; Chongxuan Liu (Journal of Hazardous Materials, 2023)

Capture of copper cyanide complex ions based on self-assembly of ionic liquids actuation and application to cyanide wastewater - Weichao Li; Wengang Liu; Wenbao Liu; Shijie Zhou; Shuling Gao; Yanbai Shen (Hydrometallurgy, 2023)

A comprehensive investigation of engineering geological characteristics of interlayer shear weakness zones embedded within Baihetan hydropower station - Gang Han; Chuanqing Zhang; Hemant Kumar Singh; Shuling Huang; Hui Zhou; Yang Gao (Tunnelling and Underground Space Technology, 2023)

Diverse viruses of marine archaea discovered using metagenomics - Yifan Zhou; Liang Zhou; Shuling Yan; Lanming Chen; Mart Krupovic; Yongjie Wang (Environmental Microbiology, 2023)
During the past decade, metagenomics became a method of choice for the discovery of novel viruses. However, host assignment for uncultured viruses remains challenging, especially for archaeal viruses, which are grossly undersampled compared to viruses of bacteria and eukaryotes. Here, we assessed the utility of CRISPR spacer targeting, tRNA gene matching and homology searches for viral signature proteins, such as major capsid proteins, for the assignment of archaeal hosts and validated these approaches on metaviromes from Yangshan Harbor (YSH). We report 35 new genomes of viruses which could be confidently assigned to hosts representing diverse lineages of marine archaea. We show that the archaeal YSH virome is highly diverse, with some viruses enriching the previously described virus groups, such as magroviruses of Marine Group II Archaea (Poseidoniales), and others representing novel groups of marine archaeal viruses. Metagenomic recruitment of Tara Oceans datasets on the YSH viral genomes demonstrated the presence of YSH Poseidoniales and Nitrososphaeria viruses in the global oceans, but also revealed the endemic YSH‐specific viral lineages. Furthermore, our results highlight the relationship between the soil and marine thaumarchaeal viruses. We propose three new families within the class Caudoviricetes for the classification of the five complete viral genomes predicted to replicate in marine Poseidoniales and Nitrososphaeria, two ecologically important and widespread archaeal groups. This study illustrates the utility of viral metagenomics in exploring the archaeal virome and provides new insights into the diversity, distribution and evolution of marine archaeal viruses.

Experimental and numerical study on seismic performance of precast segmental CFST bridge columns with non-uniform prestressed steel tendons - Dan Zhang; Zihao Zhou; Shuling Gao; Yanan Yue; Yafei Zhang; Ning Li (Engineering Structures, 2023)

Research on carbon emission measurement and low-carbon path of regional industry - Xue Wu; Shuling Zhou; Guowei Xu; Conghu liu; Yingyan Zhang (Environmental Science and Pollution Research, 2022)

Low-carbon technology service mode with revenue-sharing contract considering advance funding risk - Huiying Mao; Yuxia Guo; Yingyan Zhang; Shuling Zhou; Conghu Liu (Environmental Science and Pollution Research, 2022)

Data-driven evaluation and optimization of the sustainable development of the logistics industry: case study of the Yangtze River Delta in China - Heping Ding; Yujia Liu; Yingyan Zhang; Shuxia Wang; Yuxia Guo; Shuling Zhou; Conghu Liu (Environmental Science and Pollution Research, 2022)

Correction to: Data-driven analysis and evaluation of regional agriculture for high quality development of Anhui Province in the Yangtze River Delta - Fan Liu; Cui Wang; Yingyan Zhang; Shuling Zhou; Yaliu Yang; Xue Wu; Fagang Hu; Conghu Liu (Environmental Science and Pollution Research, 2022)

Data-driven analysis and evaluation of regional agriculture for high-quality development of Anhui Province in the Yangtze River Delta - Fan Liu; Cui Wang; Yingyan Zhang; Shuling Zhou; Yaliu Yang; Xue Wu; Fagang Hu; Conghu Liu (Environmental Science and Pollution Research, 2022)

Correction to: Complete genome sequence analysis of the Vibrio owensii strain SH‑14 isolated from shrimp with acute hepatopancreatic necrosis disease - Xiaosha Liang; Liang Zhou; Shuling Yan; Yongjie Wang (Archives of Microbiology, 2020)

Complete genome sequence analysis of the Vibrio owensii strain SH-14 isolated from shrimp with acute hepatopancreatic necrosis disease - Xiaosha Liang; Liang Zhou; Shuling Yan; Yongjie Wang (Archives of Microbiology, 2020)

Patterns of variation of the major histocompatibility complex class IIB loci in Chinese goose (Anser Cygnoides) - Xu Zhou; Chunjin Li; Kangle Yi; Hongyan Liang; Lu Chen; Yanling Sun; Shuling Niu; Wei Wu (Immunogenetics, 2009)